Ryttarens tygelsignalers inverkan på hästens beteende och trycket i tyglarna - Eisersiö, Marie (2010)
This essay derives from the concern that horses ridden with a bit in their mouth can be subjected to strong pressure from the bit if the horse and rider do not understand each other. The horse's mucosa membrane and the tongue are very sensitive tissues (Cook, 1999; Manfredi, 2005; Oliveira, 2005; Terada, 2006) and the bit can then be a source of pain and discomfort. The training of the horse should therefore always be a step by step process and as the horse develops difficulties are increased. Oliveira (2005) suggested that high demands can be placed on the horse but to be successful in the training it is essential to be content with small progress and reward the slightest desired response from the horse. This corresponds with the principles of operant conditioning with negative reinforcement. On this basis an interest was formed to study the rider's rein signals to the horse with the focus on the horse's behaviour and the pressure created through the reins.